2013
DOI: 10.1177/0004867413491154
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of psychoeducation for depression: A systematic review

Abstract: Psychoeducation is a psychosocial treatment that has been well documented as an adjunct to pharmacological therapy. However, there are only a few studies regarding its effectiveness on adult patients with major depressive disorder. Although the publications in this area are still very limited, the articles selected in this review suggest that psychoeducation is effective in improving the clinical course, treatment adherence, and psychosocial functioning of depressive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
78
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(97 citation statements)
references
References 54 publications
3
78
0
8
Order By: Relevance
“…The relief from depressive symptoms and the improved perceived control of depressive symptoms are in line with findings in other studies of the effect of cognitive behavioral therapy (Barber and DeRubeis, 1989; Cuijpers, 1998; Clark et al, 2008; Tursi et al, 2013). It is assumed that psychological treatments operate through relatively specific therapeutic processes, but at the same time apparently diverse treatments often have similar effects.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The relief from depressive symptoms and the improved perceived control of depressive symptoms are in line with findings in other studies of the effect of cognitive behavioral therapy (Barber and DeRubeis, 1989; Cuijpers, 1998; Clark et al, 2008; Tursi et al, 2013). It is assumed that psychological treatments operate through relatively specific therapeutic processes, but at the same time apparently diverse treatments often have similar effects.…”
Section: Discussionsupporting
confidence: 89%
“…Cognitive behavioral therapy and psychoeducation may increase the awareness of early signs and symptoms of relapsing, and strengthen self-efficacy in coping with depression (Bockting et al, 2009; Tursi et al, 2013). It has been suggested that psychological treatments work through changes in perceived control of depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Relatively few trials have investigated the effect of FPE on major depression [18]. One recent randomized trial found that if relatives received a brief intervention consisting of FPE, the patients who had achieved full or partial remission from an acute depressive episode had a significantly lower relapse rate in a 9-month follow-up period compared to the control condition.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have shown this strategy to be effective in major depressive disorders (in particular relapse/recurrence prevention) [17, 18], bipolar disorders [19, 20], and schizophrenia [21] as well as for addiction [22] and anxiety disorder [23, 24]. …”
Section: Introductionmentioning
confidence: 99%